Legal Certainty of The Temporary Abolition of Rights Under Article 53 Paragraph (1) of Agrarian Law - Alivia Febriyanti; M. Hamidi Masykur; Bambang Eko Supriyadi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study discusses legal certainty in the elimination of temporary rights, namely mortgage rights, profit-sharing rights, right to ride, and agricultural land lease rights, based on Article 53 paragraph (1) of the Basic Agrarian Law (UUPA). These temporary rights are a legacy of the colonial and customary systems that still give rise to legal uncertainty and agrarian conflicts. This study uses a normative-juridical approach with a literature study of laws and regulations, legal doctrine, and literature related to the principle of legal certainty. The results of the study indicate that the elimination of temporary rights must be implemented with the principle of legal certainty that emphasizes clarity of norms, consistency of application, and procedural openness. Legal certainty, as explained by Jan Michiel Otto, refers not only to the existence of written rules, but also to the effectiveness of implementation and real benefits for the community. In the context of Article 53 of the UUPA, the elimination of temporary rights must be accompanied by the transfer of rights to more permanent and registered forms of rights, such as ownership rights or use rights, thereby providing legal guarantees for farmers and the beneficiary community. This study emphasizes that the principle of legal certainty plays a strategic role in preventing arbitrary practices, reducing agrarian conflicts, and realizing social justice. With clear and consistent regulations, the elimination of temporary rights can support equitable land ownership, strengthen legal legitimacy, and improve public welfare. These findings suggest that the successful implementation of Article 53 of the UUPA depends heavily on the harmonization of written regulations, administrative practices, and public understanding of agricultural rights.